How to solve simultaneous equations with a quadratic

Example.

" Solve the simultaneous equations

y + 4x + 1 = 0

y^2 + 5x^2 + 2x = 0 "

We can rearrange the first equation to something that we can substitute into the second equation, for example

y = -4x - 1

We then substitute this into the second equation

(-4x - 1)^2 + 5x^2 + 2x = 0

16x^2 + 8x + 1 + 5x^2 + 2x = 0

21x^2 + 10x + 1 = 0

(7x + 1)(3x + 1) = 0

Gives us the solutions

x = -1/7 and x = -1/3

We then put these values into our first equation (y = -4x - 1) to give

y = -3/7 and y = 1/3

Answered by Tilly W. Maths tutor

2650 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How to do the chain rule.


How would you differentiate 3x^4 - 2x^2 + 9x - 1


solve for x, in the form x = loga/logb for 2^(4x - 1) = 3^(5-2x) (taken from OCR June 2014 C2)


The curve has equation y = x^3 - x^2 - 5x + 7 and the straight line has equation y = x + 7. One point of intersection, B, has coordinates (0, 7). Find the other two points of intersection, A and C.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences